SUBJECT-OBJECT RELATIONS IN THE PSYCHOLOGY OF CONSCIOUSNESS - Latyshev, Oleksandr (PSYCHOLOGICAL JOURNAL, 2024)
The article formulates the purpose of consciousness, which determines the direction of research in this work as a whole, namely: consciousness and self-awareness enable the subject, in the process of thinking, to realize (understand and feel) what it is like to be «there» – in a situation that is mentally assumed, and to make a decision about his real or imaginary actions. Based on the principle of subject-object relations, the mechanisms of functioning of all types of consciousness are considered from the first person, according to the general scheme. The systemic processes of consciousness and self-awareness are described as components of the thinking circuit, which is the inner world of the subject, covered by feedback. Consciousness is the flow of the subject’s experiences of images of representations of the states of his inner world. Experiences are realized in subject-object relations, where the object is an image of the representation of a fragment of the inner world in a past state, and the subject is represented by a psychosomatic image of «I» in the context of his inner world in the state of «here and now». Such a fragment can be any independent object of the inner world in a past state, including the image of «I», which is the basis of all «self-» processes, including self-knowledge, self-awareness, self-reflection, self-reference. The result of experience is subjective reality, which the subject perceives in the forms and modalities of the subject’s perception of the external world. It is shown that the processes of consciousness and self-awareness occur simultaneously. At the same time, awareness of the objects of the external and internal worlds occurs simultaneously with the subject’s awareness of himself. This solves the problem of distinguishing between the subject himself and the other. A unified procedure of consciousness is proposed, which is a multi-loop cyclical process that includes both the cognitive components of experiences and conscious reactions of the body, sensations and emotions. The principles of formation and interaction of cycles of consciousness of various types have been studied: self-awareness, awareness of independent objects, awareness of bodily reactions, emotions, awareness of the subject-object relations themselves from the first person position.